CONSANGUINEOUS MARRIAGES: UNDERSTANDING THE RISKS, BENEFITS AND PREVENTIVE STRATEGIES (Journal of Medical & Health Sciences Review, 2026)
Background: A long-standing relationship in terms of a marriage contract between the two biological relatives, is practised in many cultures and regions in the world. While it is considered that it strengthens family relations and economic stability, it is also associated with a wide range of disorders, particularly genetic disorders.Objective: By analysing the current literature and research findings, the study aims to explore the advantages and disadvantages of cousin marriage.Methods: A narrative literature review was conducted using peer-reviewed databases, including PubMed. Scopus, Google Scholar and Web of Science. Studies that focus on social, cultural, financial and genetic implications of consanguineous marriage were included. Findings were synthesized thematically across key domains without quantitative pooling.Findings: The reviewed literature showed that consanguineous marriages are mostly associated with economic stability, social cohesion and good understanding among couples. However, some medical concerns were also identified, including higher prevalence of autosomal recessive disorders, high infant mortality and genetic disorders. The impact varies across various populations, depending on genetic counselling practices and healthcare interventions.Conclusion: While consanguineous marriages are a significant regional and cultural practice, their prospective precarious outcomes make it necessary to provide greater awareness and preventive interventions. Policies supporting counselling and increased health education can assist in reducing the potential risks while respecting traditional practices. Further research is essential to navigate how healthcare systems can mitigate these challenges promptly.